The model of solving ethical challenges with nursing based on faith in God: a new model for nurses to care during epidemics - Hamideh Azimi; Rafat Rezapour-Nasrabad; Fariba Borhani; Akram Sadat Sadat-Hoseini; Maryam Momeni (BMC, 2024)
Abstract Background The existence of various ethical challenges, the inability to resolve ethical conflicts, and, as a result, the low quality of care and the occurrence of dissatisfaction in patients and nurses have been discussed for years. By creating new ethical challenges, the Covid-19pandemic has played an important role in making the process of care for these patients more difficult and complicated. This study was conducted with the aim of designing a prescriptive model to help provide ethical-care and resolve ethical conflicts during the Covid-19pandemic. Methods In this two-stage qualitative study, a grounded theory research method was used in the first stage, and data were collected through semi-structured interviews. Sampling started purposefully and continued theoretically. In the second step, the appropriate model was designed using the three-step method proposed by Walker and Avant. Results The core concept was "behavior based on faith in God", based on which the grounded theory of "faithful nursing" and then "model of solving ethical challenges with nursing based on faith in God" were presented. The strategies of the model in three parts are strengthening the beliefs of nurse, strengthening environmental facilitators to help nurse, and strengthening situational analysis in duty diagnosis in nurse were presented. Conclusions According to this model, nurses' beliefs play a key role, and the strengthening of environmental factors play a secondary role in ethical-care.